SISTEM SOSIAL DALAM DIFUSI INOVASI LINEAR TRAP BARRIER SYSTEM PADA PENGANDALIAN HAMA TIKUS USAHATANI PADI SAWAH DI DESA ATOLANU KECAMATAN LAMBANDIA KABUPATEN KOLAKA TIMUR - Mardin Mardin (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2026)
The successful adoption of agricultural innovations is determined not only by the superiority of the technology itself but also by the social system that shapes the innovation adoption process within farming communities. The Linear Trap Barrier System is an environmentally friendly and effective technology for controlling rice field rat infestations; however, its adoption among farmers remains relatively limited. This study aimed to analyze the role of the community's social system in the diffusion of LTBS innovation for rat pest management in lowland rice farming in Atolanu Village, Lambandia District, East Kolaka Regency, Indonesia. A qualitative approach with a descriptive research design was employed. Informants were selected using the snowball sampling technique and included rice farmers, farmer group leaders, agricultural extension officers, and community leaders involved in the introduction and implementation of LTBS. Data were collected through field observations, in-depth interviews, documentation, and literature review, and were analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing and verification. The findings revealed that the social system plays a pivotal role in shaping the diffusion of LTBS innovation through three interrelated dimensions: social structure, social norms, and opinion leaders. The social structure indicated that informal relationships among farmers exerted a greater influence than formal farmer organizations in fostering trust toward the innovation. Social norms showed that the absence of collective regulations regarding LTBS implementation, together with a prevailing culture of awaiting empirical evidence before adopting new practices, contributed to the gradual diffusion of the innovation. Furthermore, village heads, farmer group leaders, agricultural extension officers, and pioneering farmers functioned as opinion leaders by strengthening farmers' confidence through exemplary practices and direct experience. Strengthening the social system through trust-based networks, social learning, and local leadership is therefore considered an effective strategy for accelerating the diffusion of LTBS innovation and promoting the sustainability of rat pest management in lowland rice farming.